Pembagian Harta Bersama Akibat Perceraian Menurut Hukum Islam: Kajian terhadap Putusan Pengadilan Agama Yogyakarta Nomor 0297/Pdt.G/2017/PA - Moch Azam Azhari (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
All God's creatures, including humans, pets, and other animals and plants, are covered by the general sunnatullah of marriage. This is the way that Allah SWT chose for His creatures to reproduce and maintain their lives. The problem of the property of each husband and wife is one of the legal consequences of marriage. Article 35 of the Marriage Law regulates joint property. Marital assets are also obtained as joint assets. In the Compilation of Islamic Law, it is stated in Article 1 letter (f) that "Marital property is property acquired either individually or jointly by husband and wife during the duration of the marriage bond and in this case is called joint property, regardless of whether it is registered in the name of person." In this research method the researcher will use a qualitative method which takes place in the Yogyakarta religious court, and the techniques used to collect data include interviews and documentation. In this research the researcher will examine the decision of the Yogyakarta religious court regarding the issue of joint property which is 40% for ex-husbands and 60% for ex-wives, using the perspective of Islamic law and a compilation of Islamic law. Because Islamic Sharia levies actually divide joint assets into two for separated couples. This is different from Islamic law which does not determine how much property a couple should have. distributed after divorce, half given to ex-wife. Considering that 83 percent of Indonesia's population is Muslim, it is important to look at issues related to the division of joint property decided by judges at the Yogyakarta Religious Court.